Thermoeconomic functional analysis applied in cogeneration systems associated to cellulose plants - Luz Silveira, J. [UNESP]; Horta Nogueira, L. A. [UNESP] (My University, 1992)
Thermoeconomic Functional Analysis is a method developed for the analysis and optimal design of improvement of thermal systems (Frangopoulos, 1984). The purpose of this work is to discuss the cogeneration system optimization using a condensing steam turbine with two extractions. This cogeneration system is a rational alternative in pulp and paper plants in regard to the Brazilian conditions. The objective of this optimization consists of minimizing the global cost of the system acquisition and operation, based on the parametrization of actual data from a cellulose plant with a daily production of 1000 tons. Among the several possible decision variables, the pressure and temperature of live steam were selected. These variables significantly affect the energy performance of the cogeneration system. The conditions which determine a lower cost for the system are presented in conclusion.
Keywords: Energy utilization; Industrial economics; Mathematical models; Optimization; Paper and pulp mills; Pressure effects; Steam turbines; Thermal effects; Thermodynamics; Cellulose plants; Condensing steam turbines; Thermoeconomic functional analysis; Cogeneration plants